Pyrogenic carbon and carbonating minerals for carbon capture and storage (PyMiCCS) part II: organic and inorganic carbon dioxide removal in an Oxisol - Vorrath, Maria-Elena; Amann, Thorben; Meyer zu Drewer, Johannes; Hagemann, Nikolas; Aldrich, Cierra; Börker, Janine; Seedtke, Maria; Becker, Joscha N.; Hagens, Mathilde; Eschenbach, Annette; Hartmann, Jens (Frontiers in Climate, 2025)
Enhanced rock weathering (ERW) and pyrogenic carbon capture and storage (PyCCS, or “biochar carbon removal”) are two promising carbon dioxide removal (CDR) techniques that can contribute to soil restoration. These technologies can be combined by co-application of rock powder and biochar or by co-pyrolysis of rock powder with biomass to produce rock-enhanced (RE) biochar. In a 27-week laboratory experiment, we quantified the carbon (C) sink development of co-applications and RE-biochars produced by co-pyrolysis of basanite rock powder with either 50 or 90 wt% willow wood or 90 wt% wheat straw. Incubators featured two elevated soil pCO2 levels (0.012 and 0.062 atm, equivalent to about 1.2 and 6.2 Vol-% CO2) in a clay-rich, nutrient-poor Oxisol, with a simulated annual rainfall of 1,600 mm. Results showed strong initial fluxes of total alkalinity (TA), dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), and major cations (Mg2+, Ca2+, K+, Na+), which decreased over time. Notably, elevated pCO2 had minimal impact on the release of DOC but doubled the TA flux from ERW. An important observation was the impact of waterlogging on water fluxes in soil columns without biochar, which lowered the amount of leached cations from rock and biochar. We defined the carbon sink (C-Sink) to include all DIC of geogenic and biogenic origin, and pyrogenic carbon from biochar. Biogenic cations were not considered as contributing to additional CO2 sequestration. For a soil application equivalent to application of 12 t ha−1, the total net C-Sink ranged from −0.1 to 30.9 t CO2 ha−1 after 27 weeks under 1.2 Vol-% CO2. We were not able to determine a change in rock weathering rates from co-pyrolysis since biogenic and geogenic cations could not be distinguished. A 20-year forecast suggests net C-Sinks between 0.5 t and 28.7 t CO2 ha−1, driven by increased contributions from weathering, alongside a C-Sink loss of carbon due to biochar mineralization. While biochar alone generally produces a larger C-Sink, co-application with rock powder fosters soil remineralization and provides a higher permanence of the C-Sink. Additionally, biochar increases water-holding capacity, prevents waterlogging of soils and likely improves the retention of organic carbon in soils.